Penerapan Algoritma Even-Rodeh Code pada Istilah Dalam Peramuka - Hutauruk, Teti Sri Devi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The larger the text size compared to the quality of the text produced, the greater the size of the text needed. By looking at the compressing needs of a text, compression is needed to compress the text, can be used on external media storage space, reduce the need for bandwidth, and compress with a greater ratio than the results before compression. Regarding the solution to this problem is how this text can be used for compression to reduce usage in media storage space. Compression is done by reducing the size of the text by the process of reducing bits in the text, but does not eliminate the information data in it. By doing a large text compression will reduce its size so as to save storage space. In this study, the algorithm used is even-rodeh code by using this algorithm compression results will save more memory